Solution of the Diophantine Equation 143a + 665b = c2 - Thakur, Dinesh; Kumar, Sunil (Journal of Advanced Research in Applied Mathematics and Statistics; Vol 10 (2025): (Special Issue): Journal of Advanced Research in Applied Mathematics and Statistics, 2025)
In this manuscript, authors studied the Diophantine equation 143𝑎 + 665𝑏 = 𝑐2, where 𝑎,𝑏,𝑐 are non-negative integers, and proved that (𝑎, 𝑏, 𝑐) = (1,0,12) is the unique non-negative integer solution of this Diophantine equation.